Unveiling species diversity within the toxic diatom genus Pseudo-nitzschia from the fjords and channels of Magallanes (48°- 51° S), Chile. (February 2023) - Pinto-Torres, Marco; Pizarro, Gemita; York, Robert B.; Alves-de-Souza, Catharina; Lundholm, Nina; Mardones, Jorge I.; Nariño, María J.; Iriarte, José L.
Highlights: Pseudo-nitzschia in high latitude systems, Fjord and Channel Systems. Determination of the presence of the groups Pseudo-nitzschia delicatissima and Pseudo-nitzschia seriata. Update of the Pseudo-nitzschia species present in the southern zone of the Austral Pacific Ocean, Chile. Abstract: Species of the potentially toxic diatom genus Pseudo-nitzschia are common components of the phytoplankton community in the fjords and channel systems of the Magallanes Subantarctic region. Despite Pseudo-nitzschia species forming recurrent harmful algal blooms (HABs) in this region, Chilean monitoring programs have historically simply grouped species of this genus into two groups ( P . group seriata and P . group delicatissima ) according to basic cell morphology under light microscopy, or as Pseudo-nitzschia spp. Based on ultrastructural features obtained from scanning electron microscopy (SEM), this study revealed more diversity within the genus than previously thought, identifying six Pseudo-nitzschia species in the Magallanes Subantarctic region (48°-56°S) from samples collected during a 11-year period (2006–2017). Most importantly, the study: 1) represent the first report on diversity and distribution of Pseudo-nitzschia species in this Patagonian region; 2) expanded the known distribution of P. australis and P. fraudulenta along the Chilean coast (down to 50° S); 3) confirmed previous records of P. pungens and P. cf. delicatissima ; and 4) formally confirm the presence of P. heimii and P. calliantha in subantartic waters.